Cerium cadmium-bismuth titanate based high-temperature piezoelectric ceramic material and preparation method thereof
By introducing Ce4+/Cr3+ into Bi4Ti3O12, the preparation of cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic materials was solved, and the existing ceramic materials were achieved with high Curie temperature and excellent piezoelectric performance.
Patent Information
- Application Number
- CN202411971061.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing high-temperature piezoelectric ceramic materials have low Curie temperature and depolarization temperature, which cannot be suitable for high-temperature working environments, and the piezoelectric performance improvement of bismuth layered ceramics is limited.
By introducing Ce4+/Cr3+ into Bi4Ti3O12, cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic materials are prepared, and components and processes are optimized to improve the Curie temperature and piezoelectric properties of the ceramics.
High Curie temperature (Tc ~ 659 ℃) and good temperature stability were achieved, and excellent piezoelectric properties (d33 ~ 19.5pC/N) were obtained, which promoted the development of high-temperature piezoelectric ceramics.
Smart Images

Figure CN119912255A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature piezoelectric ceramic materials, in particular to a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material and a preparation method thereof. Background Art
[0002] As a functional material that can convert mechanical energy into electrical energy, piezoelectric ceramics have been widely used in various industrial fields. However, military industry, metallurgy, geological exploration, aerospace, nuclear energy and other fields require piezoelectric materials to have a higher Curie temperature, because these fields need to monitor the vibration and manage the health of key equipment in harsh environments such as high temperature, high radiation, and complex vibration. c ) is the critical point where ferroelectrics transform into paraelectrics. When the spontaneous polarization intensity of piezoelectric ceramics is above the Curie temperature, it becomes zero and the piezoelectric response disappears. At present, lead zirconate titanate (PZT) series piezoelectric ceramics are widely used due to their high piezoelectric and electromechanical properties, but their Curie temperature and depolarization temperature are low, which makes them inapplicable to high-temperature working environments. However, there are very few piezoelectric ceramic materials with excellent performance and high working temperature. This has led to the use of piezoelectric single crystal materials with complex production processes and high costs for special high-temperature piezoelectric devices for a long time. Therefore, it has become a top priority to develop high-Curie piezoelectric ceramic materials with excellent piezoelectric properties.
[0003] Bismuth layered piezoelectric ceramics have high Curie temperature, strong spontaneous polarization, low dielectric constant, good temperature stability, and high mechanical quality factor, making them suitable as piezoelectric materials for high temperature and high frequency applications. Therefore, they have received extensive attention and research. 12 As the earliest discovered bismuth layered ceramic, its Curie temperature is as high as 675℃. However, its low piezoelectric constant and high temperature resistivity lead to large leakage current, which seriously restricts the practical application of BIT piezoelectric ceramics in high temperature fields. Therefore, domestic and foreign researchers have improved the piezoelectric properties of bismuth layered ceramics by adopting process modification or trace element doping modification. By introducing Nb 5+ In BIT ceramic materials, a certain amount of Nb 5 + Reduce its dielectric loss and increase the resistivity of ceramics; use W 6+By doping and replacing the B position of BIT ceramics, the study found that the conductivity of the doped ceramic samples decreased by 2 to 3 orders of magnitude, allowing the ceramics to withstand higher polarization voltages and improving the piezoelectric properties of the ceramic points. However, due to the two-dimensional restriction of the spontaneous polarization direction determined by its crystal structure, the improvement of its piezoelectric coefficient is very limited. There are currently two main methods for modifying bismuth layered materials: one is to modify through composition design by doping and replacing the A and B positions, or by establishing a symbiotic structure; the other is a process modification method that promotes directional growth of grains, such as rapid plasma sintering, hot forging, hot pressing, template grain growth method, etc.
[0004] The application field of bismuth layered high-temperature piezoelectric ceramics is very wide. In addition to being the core material of high-temperature piezoelectric vibration sensors, they can also be used to make high-temperature piezoelectric ceramic capacitors, high-temperature piezoelectric ceramic filters, high-temperature piezoelectric ceramic oscillators and other components. In addition, this type of material also has good ferroelectric memory properties and can be used to make components such as ferroelectric random access memory. As a type of functional material with excellent performance, bismuth layered high-temperature piezoelectric ceramics have great application potential in the production of piezoelectric components under high temperature and high-frequency working conditions. With the continuous development of science and technology, the application prospects of this type of material in various fields will be broader. Therefore, the research on bismuth layered high-temperature piezoelectric ceramics has important scientific significance and practical application value. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material and a preparation method thereof, which solves the problems raised in the above-mentioned background technology.
[0006] To achieve the above objectives, the present invention is implemented by the following technical solutions: a cerium-cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material and a preparation method thereof, the material comprising: 0.5%-10% of cerium and cadmium by weight, and 67%-99.6% of bismuth titanate by weight, the composition chemical formula of the material is:
[0007] Bi 4-x Ce x T i 2.98 Cr 0.02 O 12 .
[0008] A further improvement of the technical solution of the present invention is that in the chemical formula of the composition, x also includes any value of the following values:
[0009] The value of x is: 0.005≤x≤0.015
[0010] A further improvement of the technical solution of the present invention is that a method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material is provided, which is applied to the cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to any one of claims 1 to 2, and is characterized in that it comprises the following specific steps:
[0011] S1: According to Bi 4-x Ce x T i 2.98 Cr 0.02 O 12 The raw materials were weighed in a metered ratio, mixed and ball-milled for 12 to 24 hours, dried in an oven at 80 to 100°C for 10 to 14 hours, and then calcined in a muffle furnace to obtain Bi 4-x Ce x T i 2.98 Cr 0.02 O 12 ;
[0012] S2: Bi obtained in S1 4-x Ce x T i 2.98 Cr 0.02 O 12 After mixing, the mixture is ball-milled for 12 to 24 hours, and dried in an oven at 80 to 100° C. for 10 to 14 hours to obtain a powder;
[0013] S3: adding polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the powder, pressing the powder into a green body at a pressure of 10 MPa, and maintaining the pressure for 1 to 2 minutes to obtain a green body;
[0014] S4: The embryo body obtained in S3 is placed in a muffle furnace for debinding and then put into an isostatic press. After isostatic pressing, the embryo body is placed in a closed crucible and sintered with the powder prepared in S2 to obtain a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material.
[0015] A further improvement of the technical solution of the present invention is that the raw materials in S1 include Bi2O3, TiO2, CeO2, and Cr2O3.
[0016] A further improvement of the technical solution of the present invention is that the mass ratio of the powder, grinding balls and alcohol in S1 and S2 is 1-1.5:2:1.5-1.8, and the rotation speed of the ball mill is 300 r / min.
[0017] A further improvement of the technical solution of the present invention is that the heating rate of calcination in S1 is 3-5°C / min, the calcination temperature is 800-850°C, and the heat preservation time is 4-5h.
[0018] A further improvement of the technical solution of the present invention is that the mass concentration of the polyvinyl alcohol aqueous solution in S3 is 5 to 10 wt %.
[0019] A further improvement of the technical solution of the present invention is that the heating rate of the binder removal in S4 is 1-5°C / min, the binder removal temperature is 600°C, and the temperature is kept for 2-4h.
[0020] A further improvement of the technical solution of the present invention is that in S4, the isostatic pressing pressure is 100-120 MPa, and the holding time is 30 minutes.
[0021] A further improvement of the technical solution of the present invention is that the heating rate of sintering in S4 is 5°C / min, the sintering temperature is 1060-1120°C, and the heat preservation time is 2-3h.
[0022] Beneficial Effects
[0023] The present invention provides a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material and a preparation method thereof. Compared with the prior art, it has the following beneficial effects:
[0024] The cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material and its preparation method are based on Bi4Ti3O 12 As the matrix, Ce is introduced 4+ / Cr 3+ , successfully prepared a high Curie temperature (T c ~659℃) and good temperature stability, and through component regulation and process optimization, excellent piezoelectric properties (d 33 ~19.5pC / N), which promoted the further development of high-temperature piezoelectric ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the process for preparing warm piezoelectric ceramic materials;
[0026] Figure 2 for Bi 4-x Ce x T i 2.98 Cr 0.02 O 12 XRD patterns of ceramics;
[0027] Figure 3 for Bi 4-x Ce x Ti 2.98 Cr 0.02 O 12 Graph showing the relationship between the dielectric constant of ceramics and temperature;
[0028] Figure 4 for Bi 4-x Ce x T i 2.98 Cr 0.02 O 12Schematic diagram of the piezoelectric constant d3 of ceramics at different annealing temperatures;
[0029] Figure 5 The following is a performance comparison table of Example 1, Example 2, Example 3 and a comparative example. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention provides a cerium-cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material and a preparation method thereof. The material comprises: 0.5% to 10% of cerium and cadmium by weight, and 67% to 99.6% of bismuth titanate by weight. The composition chemical formula of the material is:
[0032] Bi 4-x Ce x Ti 2.98 Cr 0.02 O 12 .
[0033] In the chemical formula of the composition, x also includes any value of the following values:
[0034] The value of x is: 0.005≤x≤0.015
[0035] The present invention also provides a method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material, comprising the following specific steps:
[0036] S1: According to Bi 4-x Ce x T i 2.98 Cr 0.02 O 12 The raw materials were weighed in a metered ratio, mixed and ball-milled for 12 to 24 hours, dried in an oven at 80 to 100°C for 10 to 14 hours, and then calcined in a muffle furnace to obtain Bi 4-x Ce x T i 2.98 Cr 0.02 O 12 ;
[0037] S2: Bi obtained in S1 4-x Ce x T i 2.98 Cr 0.02 O 12After mixing, the mixture is ball-milled for 12 to 24 hours, and dried in an oven at 80 to 100° C. for 10 to 14 hours to obtain a powder;
[0038] S3: adding polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the powder, pressing the powder into a green body at a pressure of 10 MPa, and maintaining the pressure for 1 to 2 minutes to obtain a green body;
[0039] S4: The embryo body obtained in S3 is placed in a muffle furnace for debinding and then put into an isostatic press. After isostatic pressing, the embryo body is placed in a sealed crucible and sintered with the powder prepared in S2 to obtain a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material.
[0040] The raw materials in S1 include Bi2O3, TiO2, CeO2, and Cr2O3.
[0041] The mass ratio of the powder, grinding balls and alcohol in S1 and S2 is 1-1.5:2:1.5-1.8, and the rotation speed of the ball mill is 300 r / min.
[0042] The heating rate of calcination in S1 is 3-5°C / min, the calcination temperature is 800-850°C, and the heat preservation is 4-5h.
[0043] The mass concentration of the polyvinyl alcohol aqueous solution in S3 is 5-10wt%.
[0044] The heating rate of the debinding in S4 is 1-5°C / min, the debinding temperature is 600°C, and the temperature is kept for 2-4h.
[0045] In S4, the isostatic pressing pressure is 100-120 MPa, and the holding time is 30 min.
[0046] The heating rate of sintering in S4 is 5°C / min, the sintering temperature is 1060-1120°C, and the temperature is kept for 2-3h.
[0047] Example 1, when the value of x is 0.0005:
[0048] S1: According to Bi 3.995 Ce 0.005 Ti 2.98 Cr 0.02 O 12 The raw materials were weighed in a stoichiometric ratio, mixed and ball-milled for 24 h, dried in an oven at 100 °C for 10 h, and then calcined in a muffle furnace at 850 °C and kept warm for 4 h (the heating rate of calcination was 3 °C / min) to obtain Bi 3.995 Ce 0.005 Ti 2.98 Cr 0.02 O 12 ;
[0049] S2: Bi obtained from S13.995 Ce 0.005 T i 2.98 Cr 0.02 O 12 After mixing, the mixture was ball-milled for 24 h and dried in an oven at 100 °C for 10 h to obtain a powder;
[0050] S3: adding 7 wt % polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the mixture, pressing the mixture under a pressure of 10 MPa to form a cylindrical body with a diameter of 10 mm and a thickness of 1 mm, and maintaining the pressure for 2 minutes to obtain a body;
[0051] S4: placing the green body described in S3 in a muffle furnace for debinding and then placing it in an isostatic press. After isostatic pressing, placing it in a closed crucible, burying and sintering the powder prepared in S2, and obtaining the cerium cadmium-bismuth titanate-based high temperature piezoelectric ceramic material
[0052] The debinding conditions are as follows: heating rate of 5°C / min, debinding temperature of 600°C, and keeping temperature for 3h.
[0053] The isostatic pressing conditions are: pressure of 120 MPa and holding time of 30 min.
[0054] The sintering conditions are as follows: heating rate of 5°C / min, sintering temperature of 1060°C, and keeping temperature for 3h.
[0055] The ball milling conditions in S1 and S2 were as follows: the mass ratio of powder, grinding balls and alcohol was 1:2:1.5, and the ball mill speed was 300 r / min.
[0056] Example 2, when x is 0.010:
[0057] S1: According to Bi 3.990 Ce 0.010 Ti 2.98 Cr 0.02 O 12 The raw materials were weighed in a stoichiometric ratio, mixed and ball-milled for 24 h, dried in an oven at 100 °C for 10 h, and then calcined in a muffle furnace at 850 °C and kept warm for 4 h (the heating rate of calcination was 3 °C / min) to obtain Bi 3.990 Ce 0.010 T i 2.98 Cr 0.02 O 12 ;
[0058] S2: Bi obtained from S1 3.990 Ce 0.010 T i 2.98 Cr 0.02 O 12 After mixing, the mixture was ball-milled for 24 h and dried in an oven at 100 °C for 10 h to obtain a powder;
[0059] S3: adding 7 wt % polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the mixture, pressing the mixture under a pressure of 10 MPa to form a cylindrical body with a diameter of 10 mm and a thickness of 1 mm, and maintaining the pressure for 2 minutes to obtain a body;
[0060] S4: placing the green body described in S3 in a muffle furnace for debinding and then placing it in an isostatic press. After isostatic pressing, placing it in a closed crucible, burying and sintering the powder prepared in S2, and obtaining the cerium cadmium-bismuth titanate-based high temperature piezoelectric ceramic material
[0061] The debinding conditions are as follows: heating rate of 5°C / min, debinding temperature of 600°C, and keeping temperature for 3h.
[0062] The isostatic pressing conditions are: pressure of 120 MPa and holding time of 30 min.
[0063] The sintering conditions are as follows: heating rate of 5°C / min, sintering temperature of 1060°C, and keeping temperature for 3h.
[0064] The ball milling conditions in S1 and S2 were as follows: the mass ratio of powder, grinding balls and alcohol was 1:2:1.5, and the ball mill speed was 300 r / min.
[0065] Example 3, when x is 0.015:
[0066] S1: According to Bi 3.985 Ce 0.015 T i 2.98 Cr 0.02 O 12 The raw materials were weighed in a stoichiometric ratio, mixed and ball-milled for 24 h, dried in an oven at 100 °C for 10 h, and then calcined in a muffle furnace at 850 °C and kept warm for 4 h (the heating rate of calcination was 3 °C / min) to obtain Bi 3.985 Ce 0.015 T i 2.98 Cr 0.02 O 12 ;
[0067] S2: Bi obtained from S1 3.985 Ce 0.015 T i 2.98 Cr 0.02 O 12 After mixing, the mixture was ball-milled for 24 h and dried in an oven at 100 °C for 10 h to obtain a powder;
[0068] S3: adding 7 wt % polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the mixture, pressing the mixture under a pressure of 10 MPa to form a cylindrical body with a diameter of 10 mm and a thickness of 1 mm, and maintaining the pressure for 2 minutes to obtain a body;
[0069] S4: placing the green body described in S3 in a muffle furnace for debinding and then placing it in an isostatic press. After isostatic pressing, placing it in a closed crucible, burying and sintering the powder prepared in S2, and obtaining the cerium cadmium-bismuth titanate-based high temperature piezoelectric ceramic material
[0070] The debinding conditions are as follows: heating rate of 5°C / min, debinding temperature of 600°C, and keeping temperature for 3h.
[0071] The isostatic pressing conditions are: pressure of 120 MPa and holding time of 30 min.
[0072] The sintering conditions are as follows: heating rate of 5°C / min, sintering temperature of 1060°C, and keeping temperature for 3h.
[0073] The ball milling conditions in S1 and S2 were as follows: the mass ratio of powder, grinding balls and alcohol was 1:2:1.5, and the ball mill speed was 300 r / min.
[0074] Example 4: In order to facilitate observation of the performance improvement of the cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material proposed in this application, this example provides a comparative example, specifically:
[0075] S1: According to Bi4Ti3O 12 The raw materials were weighed in a stoichiometric ratio, mixed and ball-milled for 24 h, dried in an oven at 100 °C for 10 h, and then calcined in a muffle furnace at 850 °C and kept warm for 4 h (the heating rate of calcination was 3 °C / min) to obtain Bi4Ti3O 12 ;
[0076] S2: Bi4Ti3O prepared in S1 12 After mixing, the mixture was ball-milled for 24 h and dried in an oven at 100 °C for 10 h to obtain a powder;
[0077] S3: adding 7 wt % polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the mixture, pressing the mixture under a pressure of 10 MPa to form a cylindrical body with a diameter of 10 mm and a thickness of 1 mm, and maintaining the pressure for 2 minutes to obtain a body;
[0078] S4: placing the green body described in S3 in a muffle furnace for debinding and then placing it in an isostatic press. After isostatic pressing, placing it in a closed crucible, burying and sintering the powder prepared in S2, and obtaining the cerium cadmium-bismuth titanate-based high temperature piezoelectric ceramic material
[0079] The ceramic materials obtained in Example 1, Example 2, Example 3 and the control group were ground, plated with electrodes and polarized. The polarization electric field was 6-10 kV / mm, the polarization time was 30 min, and the polarization temperature was 180°C. The piezoelectric properties of the products were measured as shown in the attached figure. Figure 5 shown.
[0080] As can be seen from the attached figure, with the4+ / Cr 3+ The introduction of piezoelectric ceramics 33 Both have been significantly improved. c Compared with the control example, there is a slight decrease. When x = 0.010, d 33 The highest, up to 19.5pC / N, T c It is still 659℃, with the best overall performance.
[0081] In order to further explore and prove the performance of cerium cadmium-bismuth titanate based high temperature piezoelectric ceramic materials, Figure 2 The XRD patterns of the ceramic materials obtained in Example 1, Example 2, Example 3 and the comparative example of the present invention are shown. All samples have the strongest diffraction peak (117) at about 30°, which is consistent with the Bi4Ti3O 12 Orthorhombic phase structure, no second phase was detected in the diffraction peak, reflecting that no impurity phase was produced during the sintering process;
[0082] Attached Figure 3 The dielectric constant of samples with different doping amounts varies with temperature. 4+ / Cr 3+ The introduction of dopants increases the Curie temperature T c It shows a downward trend, but the decline is very small, and the Curie temperature is still above 650℃;
[0083] Attached Figure 4 The piezoelectric constant of samples with different doping amounts varies with annealing temperature. It can be seen that Ce 4+ / Cr 3+ Co-doped ceramic material 33 The temperature stability is significantly improved and it shows good temperature stability in the temperature range of 25-500℃. 33 Maintain above 80% of normal temperature.
[0084] In summary, the cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material prepared in the present application has a high Curie temperature, good temperature stability and excellent piezoelectric properties.
[0085] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art, and the model parameters of each electrical appliance are not specifically limited, and conventional equipment can be used.
[0086] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material, characterized in that: The material comprises: 0.5% to 10% of cerium and cadmium in total weight, and 67% to 99.6% of bismuth titanate in total weight. The chemical formula of the material composition is: Bi 4-x What x IT 2.98 -R 0.02 A 12 。 2. The cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 1, characterized in that: In the chemical formula of the composition, x also includes any value of the following values: The value of x is: 0.005≤x≤0.
015.
3. A method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material, applied to the cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to any one of claims 1-2, characterized in that: The specific steps include: S1: According to Bi 4-x Ce x Ti 2.98 Cr 0.02 O 12 The raw materials were weighed in a metering ratio, mixed and ball-milled for 12 to 24 hours, dried in an oven at 80 to 100°C for 10 to 14 hours, and then calcined in a muffle furnace to obtain Bi. 4-x Ce x Ti 2.98 Cr 0.02 O 12 ; S2: Bi obtained in S1 4-x Ce x Ti 2.98 Cr 0.02 O 12 After mixing, the mixture is ball-milled for 12 to 24 hours, and dried in an oven at 80 to 100° C. for 10 to 14 hours to obtain a powder; S3: adding polyvinyl alcohol aqueous solution to the powder obtained in S2, grinding the powder, pressing the powder into a green body at a pressure of 10 MPa, and maintaining the pressure for 1 to 2 minutes to obtain a green body; S4: The embryo body obtained in S3 is placed in a muffle furnace for debinding and then put into an isostatic press. After isostatic pressing, the embryo body is placed in a sealed crucible and sintered with the powder prepared in S2 to obtain a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material.
4. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: The raw materials in S1 include Bi2O3, TiO2, CeO2, and Cr2O3.
5. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: The mass ratio of the powder, grinding balls and alcohol in S1 and S2 is 1-1.5:2:1.5-1.8, and the rotation speed of the ball mill is 300 r / min.
6. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: The heating rate of calcination in S1 is 3-5°C / min, the calcination temperature is 800-850°C, and the heat preservation is 4-5h.
7. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: The mass concentration of the polyvinyl alcohol aqueous solution in S3 is 5-10wt%.
8. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: The heating rate of the debinding in S4 is 1-5°C / min, the debinding temperature is 600°C, and the temperature is kept for 2-4h.
9. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: In S4, the isostatic pressing pressure is 100-120 MPa, and the holding time is 30 min.
10. The method for preparing a cerium cadmium-bismuth titanate-based high-temperature piezoelectric ceramic material according to claim 3, characterized in that: The heating rate of sintering in S4 is 5°C / min, the sintering temperature is 1060-1120°C, and the temperature is kept for 2-3h.
Citation Information
Patent Citations
Multielement-doped bismuth titanate group lead-free piezoceramic material and preparation method thereof
CN102167585A
Calcium bismuth titanate-based piezoelectric ceramic material and preparation method thereof
CN116120054A
High-temperature piezoelectric ceramic compositions
CN1424283A
Piezoelectric ceramic composition and piezoelectric element
JP2013155079A
Potassium bismuth titanate piezoelectric body, method for producing same, piezoelectric elemennt and piezoelectric functional device
WO2021172474A1